HUBUNGAN REGULASI DIRI DENGAN KECEMASAN MENGHADAPI UJIAN SKRIPSI PADA MAHASISWA PROGRAM STUDI PENDIDIKAN EKONOMI UNIVERSITAS MUHAMMADIYAH PURWOREJO - Cahyana Nursidiq (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2016)
The aim of this research is to find out the relationship between self-regulation and anxiety in facing thesis examination on the the students of Economics Education, Faculty of Teacher Training And Educational Sciences Muhammadiyah University of Purworejo. The research was conducted from January until June 2013 in Economics Education, Faculty of Teacher Training and Educational Sciences Muhammadiyah University of Purworejo. Method applied in this research was survey method. Fifty students are taken as respondents in which they are thesis examination takers on period 2 and 3 in 2013. Variables observed are self-regulation and anxiety in facing thesis examination. Data were analysed by using descriptive analysis and rank spearman. Questionares were examined by using validity and reliability validity. From the correation analysis result (r), it is obtained correlation between self-regulation and and anxiety in facing thesis examination as much as - 0,606. This result shows there is strong relationship between self-regulation and and anxiety in facing thesis examination. While relationship flow is negative because r value is negative. This fact shows high self–regulation will result low anxiety in facing thesis examination.